Combining local knowledge and soil science for integrated soil health assessments in conservation agriculture systems - Hermans, T.D.G.; Dougill, Andrew J.; Whitfield, S.; Peacock, C.L.; Eze, S.; Thierfelder, Christian L. (Elsevier, 2021)
The challenges of soil degradation and climate change have led to the emergence of Conservation Agriculture (CA) as a sustainable alternative to tillage-based agriculture systems. Despite the recognition of positive impacts on soil health, CA adoption in Africa has remained low. Previous soil health studies have mainly focused on ‘scientific’ measurements, without consideration of local knowledge, which influences how farmers interpret CA impacts and future land management decisions. This study, based in Malawi, aims to 1) combine local knowledge and conventional soil science approaches to develop a contextualised understanding of the impact of CA on soil health; and 2) understand how an integrated approach can contribute to explaining farmer decision-making on land management. Key farmers' indicators of soil health were crop performance, soil consistence, moisture content, erosion, colour, and structure. These local indicators were consistent with conventional soil health indicators. By combining farmers' observations with soil measurements, we observed that CA improved soil structure, moisture (Mwansambo 7.54%–38.15% lower for CP; Lemu 1.57%–47.39% lower for CP) and infiltration (Lemu CAM/CAML 0.15 cms−1, CP 0.09 cms−1; Mwansambo CP/CAM 0.14 cms−1, CAML 0.18 cms−1). In the conventional practice, farmers perceived ridges to redistribute nutrients, which corresponded with recorded higher exchangeable ammonium (Lemu CP 76.0 mgkg −1, CAM 49.4 mgkg −1, CAML 51.7 mgkg −1), nitrate/nitrite values (Mwansambo CP 200.7 mgkg −1, CAM 171.9 mgkg −1, CAML 103.3 mgkg −1). This perception contributes to the popularity of ridges, despite the higher yield measurements under CA (Mwansambo CP 3225 kgha-1, CAML 5067 kgha-1, CAM 5160 kgha-1; Lemu CP 2886 kgha-1, CAM 2872 kgha-1, CAML 3454 kgha-1 ). The perceived carbon benefits of residues and ridge preference has promoted burying residues in ridges. Integrated approaches contribute to more nuanced and localized perceptions about land management. We propose that the stepwise integrated soil assessment framework developed in this study can be applied more widely in understanding the role of soil health in farmer-decision making, providing a learning process for downscaling technologies and widening the evidence base on sustainable land management practices.